Microplastic distribution in the fish flesh as physical pollutants: Preliminary study - Ezraneti, Riri; Hassan, Noor Artika; Miskon, Mohd Fuad; Mohamed, Juliana (Universitas Malikussaleh, 2025)
Microplastics, as physical pollutants, have become a hazard and can accumulate in fish tissues. There is limited documentation of the spread of microplastic buildup in fish flesh. The purpose of this research was to investigate the distribution of microplastics in fish flesh. This study used the golden threadfin bream (Nemipterus virgatus) as one of the commercial marine fish in peninsular Malaysia. The fish was dissected by filleting and separated through its dorsal, ventral, and caudal parts to observe if there was variation in the accumulation of microplastics in each part of the fish flesh. The findings show that the caudal part has the most microplastic accumulation compared to the dorsal and ventral parts. However, there is no significant difference in the amount of microplastic discovered in any part of the fish based on statistical analysis. The bulk of the microplastics identified are black and have a fibre form. Polyamide (PA), polyethylene terephthalate (PET), and polypropylene are types of microplastics found in the fish flesh. This research shows that microplastics can accumulate in every part of the fish flesh in varying amounts. To accurately depict the average number of microplastics in fish flesh, it is recommended to randomly sample the fish flesh for detection.